Associations between peripheral perfusion disorders, mean arterial pressure and dose of norepinephrine administrated in the early phase of septic shock. (5th July 2021) - Magnin, Mathieu; Amson, Harry; Vacheron, Charles‐Hervé; Thiollière, Fabrice; Piriou, Vincent; Junot, Stéphane; Bonnet Garin, Jeanne‐Marie; Allaouchiche, Bernard
Abstract: The aim of the study was to explore the correlations between peripheral perfusion, mean arterial pressure and the dose‐rate of norepinephrine (NE) infused for the treatment of septic shock. The study is retrospective analysis of data acquired prospectively on 57 patients during the first 24 hours after the occurrence of the shock. Clinical and haemodynamic characteristics, skin perfusion parameters (capillary refill time [CRT], mottling score and temperature gradients) and the dose rate of NE infusion were collected. Negative correlations between mean arterial pressure (MAP) and temperature gradients (core‐to‐toe: P = .03, core‐to‐index: P = .04) were found and abnormal CRT was associated with lower MAP ( P = .02). The dose rate of NE was negatively correlated with temperature gradients (core‐to‐toe: P = .02, core‐to‐index: P = .01, forearm‐to‐index: P = .008) in the overall population. In patients receiving NE for at least 12 hours, the NE dose rate positively was correlated with the mottling score ( P = .006), temperature gradients (core‐to‐toe: P = .04, forearm‐to‐index: P = .02, core‐to‐index: P = .005) and CRT ( P = .001). The dose of NE administrated was associated with 14‐days mortality (odds ration [OR] = 1.21 [1.06‐1.38], P = .006) and with 28‐days mortality (OR = 1.17 [1.01‐1.36], P = 0.04). In conclusion, the study described the presence of correlations between peripheral perfusion and MAP and between peripheral perfusion and the dose rate of NE infusion.